RELASI PEDAGOGIS ORANG TUA DAN ANAK DALAM MENGEMBANGKAN KECERDASAN MAJEMUK PADA DIRI ANAK USIA DINI - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2021)
This study aims to examine the pedagogical relationship of parents and children in developing multiple intelligences in early childhood. This research is very relevant to the efforts of parents in educating their children. The focus of this literature research is to find out how the relationship between parents and children is in an effort to develop multiple intelligences in early childhood. The data collection technique used in this research is by using a literature review which is then analyzed from the perspective of the object of study. Keywords: Pedagogical Relations, Parents, Children, Multiple Intelligences